Eye laterality: a comprehensive analysis in refractive surgery candidates. (7th February 2013) - Linke, Stephan J.; Druchkiv, Vasyl; Steinberg, Johannes; Richard, Gisbert; Katz, Toam
Abstract: Purpose: To explore eye laterality (higher refractive error in one eye) and its association with refractive state, spherical/astigmatic anisometropia, age and sex in refractive surgery candidates. Methods: Medical records of 12 493 consecutive refractive surgery candidates were filtered. Refractive error (subjective and cycloplegic) was measured in each subject and correlated with eye laterality. Only subjects with corrected distance visual acuity (CDVA) of >20/22 in each eye were enrolled to exclude amblyopia. Associations between eye laterality and refractive state were analysed by means of t ‐test, chi‐squared test, Spearman's correlation and multivariate logistic regression analysis, respectively. Results: There was no statistically significant difference in spherical equivalent between right (−3.47 ± 2.76 D) and left eyes (−3.47 ± 2.76 D, p = 0.510; Pearson's r = 0.948, p < 0.001). Subgroup analysis revealed (I) right eye laterality for anisometropia >2.5 D in myopic (−5.64 ± 2.5 D versus −4.92 ± 2.6 D; p = 0.001) and in hyperopic (4.44 ± 1.69 D versus 3.04 ± 1.79 D; p = 0.025) subjects, (II) a tendency for left eye cylindrical laterality in myopic subjects, and (III) myopic male subjects had a higher prevalence of left eye laterality. (IV) Age did not show any significant impact on laterality. Conclusions: Over the full refractive spectrum, this study confirmed previously described strong interocular refractive correlation but revealed a statistically significant higher rate of right eye laterality for anisometropia >2.5 D. In general, our results support the use of data from one eye only in studies of ocular refraction.